(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Intussusception is the most common cause of intestinal obstruction in infants and young children. Objective: To review the clinical, epidemiological, management pattern and outcome of intussusception. Methods: A retrospective descriptive review of 47 patients who were diagnosed and managed for intussusception during the period from January 2012 to October 2014 in Al-Ramadi Teaching Hospital for Maternity and Children. Data were collected from the Pediatric Surgery Unit records, which include demographic characteristics of the patients, history of preceding gastroenteritis or respiratory infection, clinical signs and symptoms, imaging studies, type of management, operative finding, outcome and mortality. Data were analyzed by Epi Info7TM, using chi-square to obtain p value which regarded significant when it was < 0.05. Results: Records of 47 patients were reviewed; (68.4%) were under one year of age. Peak incidence between 6-12 months of age (55.3%). Male: female ratio was 2.35:1. 27 patients (57.4%) were from rural area, peak seasonal incidence occurred in summer and winter, 41 patients (87.2%) presented with abdominal pain, a palpable abdominal mass was detected in 24 patients (51%), red currant jelly stool reported in (74.5%). Ultrasonography were done for 39 patients and showed an abdominal mass suggestive intussusception (as a target sign or pseudo kidney mass) in 34 patients (87.1%). (95.7%) of patients treated by surgical reduction, while only two patient reduced by hydrostatic enema, Meckle’s diverticulum were the commonest pathological lead point (44.4%). No intussusception- associated death was recorded. Conclusion: Colicky abdominal pain was the most presenting symptoms and red currant stool was a significant sign especially in children ? 12 months. Majority of cases presented after 24 hours were from rural area, seasonal peaks occurred in summer and winter months and surgery remain the mode of management. Keywords: Intussusception, clinical, epidemiological, management pattern and outcome. Citation: Al-Ani MMM, Ghani SH, Maklef OK. Evaluation of intussusception in children: our experience in 47 cases. Iraqi JMS. 2017; Vol. 15(3): 250-261. doi: 10.22578/IJMS.15.3.6